Climate-resilient seed systems and access and benefit-sharing in Zambia - Nkhoma, C.N.; Otieno, G. (ISSD Africa, 2017)
This case study focuses on activities being implemented in relation to access and benefit sharing in the development of plant genetic resources for food and agriculture (PGRFA), and the availability of PGRFA for climate change adaptation. The study looked at the movement of PGRFA in and out of Zambia, and how international and national PGRFA developments have enhanced the resilience of Zambia’s seed systems. Secondary data, obtained from the Genesys database1 and the Secretariat of the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA), was analysed to show trends in flows of PGRFA in and out of the country and within the country. Primary data and information on germplasm exchange was collected from key informant surveys with people from various institutions involved in research, conservation and extension.